2022
DOI: 10.5194/egusphere-egu22-9757
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Solid-phase extraction of aquatic organic matter: loading-dependent chemical fractionation and self-assembly

Abstract: <p>Dissolved organic matter (DOM) is an important component in marine and freshwater environments and plays a fundamental role in global biogeochemical cycles. In the past, optical and molecular-level analytical techniques evolved and improved our mechanistic understanding about DOM fluxes. For most molecular chemical techniques, sample desalting and enrichment is a prerequisite. Solid-phase extraction (SPE) has been widely applied for concentrating and desalting DOM. The major aim of this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…A likely reason for this difference is that we passed about 2 mg C per gram of PPL sorbent (4-4.5 L of water), while these authors passed not more than 1 mg C per gram of sorbent, which seems to improve the recovery of DOM compounds. This assumption aligns with Kong et al (2021), who shown that increasing DOC loads led to lower DOC, absorbance and fluorescence extraction efficiencies. Furthermore, differences between studies could be due to location and/or DOM quality and quantity.…”
Section: Ppl-dom Extraction Efficiency and Selectivitysupporting
confidence: 90%
“…A likely reason for this difference is that we passed about 2 mg C per gram of PPL sorbent (4-4.5 L of water), while these authors passed not more than 1 mg C per gram of sorbent, which seems to improve the recovery of DOM compounds. This assumption aligns with Kong et al (2021), who shown that increasing DOC loads led to lower DOC, absorbance and fluorescence extraction efficiencies. Furthermore, differences between studies could be due to location and/or DOM quality and quantity.…”
Section: Ppl-dom Extraction Efficiency and Selectivitysupporting
confidence: 90%
“…As observed in other studies (Wang et al, 2019b;He et al, 2020;Pang et al, 2021) molecular formulas consisted primarily of the CHO elemental series (59-76%), followed by sulfur (12-24%) and nitrogen containing formulas (10-19%) in most samples (Table 1). For the 2010 samples, we adjusted extraction volumes to DOC concentrations to avoid loading-dependent fractionation as Kong et al (2021) suggested (Figure S1). The variation of (O/C) wa and (H/C) wa varied with the DOC loadings but did not differ between the two sampling periods.…”
Section: Spatiotemporal Variation Of the Dom Compositionmentioning
confidence: 99%
“…a 254 , FI, SUVA 254 and florescence excitations emission matrix parallel factor components (McKnight et al, 2001;He et al, 2020). Recently it has been reported that one should be careful with such comparison analyses that were performed on original water and extracted samples (e.g., Wünsch et al, 2018;Kong et al, 2021). One detailed investigation elucidated that FT-ICR-MS formulas assigned to PARAFAC components represented ~40% of the total number of formulas identified and ~60% of total FT-ICR-MS peak intensities (Stubbins et al, 2014).…”
Section: Spatiotemporal Variation Of the Dom Compositionmentioning
confidence: 99%